2007
DOI: 10.2322/jjsass.55.388
|View full text |Cite
|
Sign up to set email alerts
|

Damage Behaviors and Compressive Strength of Toughened CFRP Laminates with Thin Plies Subjected to Transverse Impact Loadings

Abstract: It has been recognized that damage resistance and strength properties of CFRP laminates can be improved by using thin-ply prepregs. This study investigates the damage behaviors and compressive strength of CFRP laminates using thin-ply and standard prepregs subjected to out-of-plane impact loadings. CFRP laminates used for the evaluation are prepared using the standard prepregs, thin-ply prepregs, and combinations of the both. Weight-drop impact test and post-impact compression test of quasi-isotropic laminates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The impact resistance of CFRPs must be improved to ensure the safety and reliability of structures. Yokozeki et al [8] have suggested that the impact resistance of CFRPs by out-of-plane impact load was improved by using the toughened CFRP laminated with thin plies. Yamada et al [9] have also proposed that the metal layers insertion in thin-ply composite laminates was improved Compressive after impact (CAI) strength by inhibiting the fiber break.…”
Section: Introductionmentioning
confidence: 99%
“…The impact resistance of CFRPs must be improved to ensure the safety and reliability of structures. Yokozeki et al [8] have suggested that the impact resistance of CFRPs by out-of-plane impact load was improved by using the toughened CFRP laminated with thin plies. Yamada et al [9] have also proposed that the metal layers insertion in thin-ply composite laminates was improved Compressive after impact (CAI) strength by inhibiting the fiber break.…”
Section: Introductionmentioning
confidence: 99%
“…The use of thin-ply prepreg was proved to have distinct effects on laminates' strength. In a study by Yokozeki et al (2007), the use of thin-ply prepreg in quasi-isotropic laminates can improve compressive-after-impact (CAI) strength of the laminates compared to prepregs with conventional thickness. They also showed that the CFRP laminates which have thin-ply prepregs at the outer surface with conventional prepregs as inner plies cured together exhibited the highest CAI strength among stacking combinations they tested.…”
Section: Introductionmentioning
confidence: 99%